Synthesis New Pyridinium Salts as Corrosion Inhibitors for Mild Steel in 1 M H2SO4 - Kareem, Rania; Salih Shihab, Mehdi (Al-Nahrain Journal of Science, 2021)
Some new pyridinium salts, namely 4-(4-Chloro-benzylidene-hydrazinocarbonyl)-1-phenyl-pyridinium bromide, C1; 4-(4-Chloro-benzylidene-hydrazinocarbonyl)-1-butyl-pyridinium bromide, C2; 4-(4-Chloro-benzylidene-hydrazinocarbonyl)-1-phencyl-pyridinium bromide, C3; were synthesized and Corrosion inhibitors for mild steel were tested in a 1M H2SO4 aqueous solution at 20 ºC for 24 hours using weight loss measurements. The findings revealed that the inhibition efficiency of all pyridinium bromide derivatives converges at the maximum concentration. An increase in inhibitor concentration is associated with a decrease in corrosion rate, an increase in inhibition efficiencies, and an increase in surface degree of coverage. The physisorption effects for (C1, C2, and C3) were revealed by the free energy values of adsorption, which provided useful information for predicting the interaction between the metal surface and organic molecules as corrosion inhibitors.